A corpus-driven study on the use of passive verb bundles in academic writing : a comparison between L1 and L2 English speakers - Radika Subramaniam,; Sheena Kaur, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lexical bundles studies are still limited in relation to the use of verb phrase-based bundles, specifically the passive forms in academic writing. This study reveals the lexico-grammatical patterns and functional categories of passive verb bundles in the 409,373-word Malaysian Polytechnics Electronic Engineering Learner Corpus (MyPolyEELC) in comparison to the British Academic Written English (BAWE) 29,530-word sub-corpus. The Sketch Engine lexical computing tool is used to analyse both the L2 Malaysian and L1 English learner writing. Biber et al.’s (1999) structural categories framework is employed to identify the verb-phrase bundles and further locate the passive forms, whereas the functional categories are identified through Hyland’s (2008a) framework. Francis et al.’s (1996) verb pattern analysis is used to identify the lexico-grammatical patterns and meaning groups of the passive verb bundles. The analyses indicate several passive verb structural categories in both learner corpora. The L2 learners disclose limited participant-oriented functions in the passive verb bundles’ use, which is contrary to the L1 English learners who display profound use of participant-oriented ‘engagement’ and ‘stance’ categories through several choices of lexical verbs. The findings also show the inter-relation between the meaning group, lexico-grammatical pattern and functional category. The inter-relationship illustrates that the meaning group which motivates the lexico-grammatical pattern or vice versa, further contributes to identification of the functional category of the bundles based on a larger context of the text. The variations discovered between the L2 and L1 learner writing may offer several corpus-related pedagogical practices to be applied in an EAP classroom.